Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Nicholas Dibiaso, Pam Ardaiz, Hon. Jim Ardaiz, Judy Henry, Hon. Stephen Henry, Carol Thaxter, Hon. James Thaxter